2018
DOI: 10.1002/acm2.12461
|View full text |Cite
|
Sign up to set email alerts
|

Occupational radiation exposure to nursing staff during cardiovascular fluoroscopic procedures: A review of the literature

Abstract: Fluoroscopy is a method used to provide real time x‐ray imaging of the body during medical procedures to assist with medical diagnosis and treatment. Recent technological advances have seen an increase in the number of fluoroscopic examinations being performed. Nurses are an integral part of the team conducting fluoroscopic investigations and are often located close to the patient resulting in an occupational exposure to radiation. The purpose of this review was to examine recent literature which investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
6
0
1
Order By: Relevance
“…Under FGAR, the intussusception patients, their parents, and the medical staff can be exposed to ionizing radiation multiple times. The accumulation of radiation in the human body within a short period of time may also cause pathological changes; exact research has shown that receiving large doses of electromagnetic radiation can cause radiation-related malignancy [23,24]. UGHR totally avoids radiation damage to human health, which is very meaningful for the protection of the patients, parents of the patients, and medical staff.…”
Section: Resultsmentioning
confidence: 99%
“…Under FGAR, the intussusception patients, their parents, and the medical staff can be exposed to ionizing radiation multiple times. The accumulation of radiation in the human body within a short period of time may also cause pathological changes; exact research has shown that receiving large doses of electromagnetic radiation can cause radiation-related malignancy [23,24]. UGHR totally avoids radiation damage to human health, which is very meaningful for the protection of the patients, parents of the patients, and medical staff.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference found between the patient BMI across the categories considered in this study, but it is recognised that the dose to the staff and patients during fluoroscopically guided coronary procedures is influenced by patient BMI 55 . Due to the complexity of anatomy, x-ray tube angulation is frequently utilized to provide effective imaging during cardiac and vascular procedures, and this has been demonstrated to greatly affect patient and staff dose 57 . Steeper angles result in higher doses to the patient due to the additional thickness of tissue for the beam to traverse 58 .…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Chen et al 10 a taxa de uso de aventais plumbíferos é baixa, por volta de 70% e quase 10% dos profissionais analisados não sabiam a posição adequada do dosímetro. Wilson-Stewart et al 11 ressaltam que a não utilização, ou a utilização incorreta destes dispositivos, pode favorecer o excesso de dose recomendado à equipe. Uma pesquisa argelina feita em 2016 indica que o uso da vestimenta correta pode reduzir para menos de 10% a exposição de dose efetiva anual em cardiologistas intervencionistas e o conjunto de avental e protetor de tireoide reduz a menos de 4% essa exposição 12 .…”
Section: Discussionunclassified